A literature review study using Proknow-C for production sequencing problems with a sustainable perspective - Silva, Arthur Guilherme Siqueira da; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2023)
Production scheduling within the supply chain is essential for an organization to succeed or fail in its business. In this way, the search for efficiency and optimization has become a subject constantly guided in the academic environment. However, over the last 20 years, the consequences of this behavior are being reverberated on our planet. Therefore, this article aims to carry out a literature review, using the ProKnow-C methodology, regarding the environmental impacts of misuse and allocation of resources during production scheduling within the stockyards. Its development was based on the selection of a bibliographic portfolio, through the academic impact, within the last five years, through keywords. After selecting the portfolio, a bibliometric and systemic analysis was carried out, where it was possible to perceive that the search for a sustainable supply chain is gaining relevance within the literature on the national scene, but it is still embryonic. Thus, it can be concluded that, by opting for a production schedule that is less harmful to the environment, it will become an essential factor in making decisions that guide a production process.
Keywords: Sustainable supply chain; Decision making; Production scheduling; Greenhouse gases